An audit of management practices in patients with suspected temporary monocular blindness. Issue 6 (1st November 2013) - Naylor, A R; Robinson, T G; Eveson, D; Burns, J
Abstract : Background: The highest risk period for suffering a stroke after a transient ischaemic attack (TIA) or temporary monocular blindness (TMB) is the first 14 days and this is the recommended threshold for performing carotid endarterectomy (CEA). However, evidence suggests that TMB patients face significant delays in starting medical therapy and undergoing CEA. This study audited management practices in an ophthalmology department, 3 years after introducing a daily TIA clinic that offered single-visit imaging and the implementation of best medical therapy. Methods: Sequential audit (July 2011, July 2012) of ophthalmology staff at Leicester Royal Infirmary. Results: TIA clinic awareness increased to 90%, but 80% remained unaware of the 14-day target for performing CEA. Most (81%) were aware that ophthalmologists could refer TMB patients to the clinic, but virtually no one used this service, preferring to request an outpatient carotid ultrasound scan and then refer on as appropriate. The majority (86% in 2012) were happy to prescribe aspirin, but virtually nobody would prescribe statins. Conclusion: There is a need to improve professional awareness of the importance of starting best medical therapy and performing CEA as soon as possible after onset of TMB.